A CONTROLLED STUDY OF AN HIV/AIDS/STI/TB INTERVENTION WITH FAITH HEALERS IN VHEMBE DISTRICT, SOUTH AFRICA - Mashamba, Tshilidzi; Peltzer, Karl; Maluleke, Thelma X; Sodi, Tholene (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The aim of the study was to develop an HIV and AIDS training manual, and to evaluate the knowledge, attitudes and management of faith healers of Apostolic churches regarding HIV and AIDS, before and after they attended an HIV and AIDS training programme. A quasi-experimental intervention design was used with faith healers affiliated with the United African Apostolic Church (UAAC) in the Thulamela and Musina municipalities of Vhembe District, Limpopo Province, South Africa. A total of 103 faith healers were included in this study, 58 were systematically assigned to an intervention and 45 to a control group. The intervention group received training for 2 days. At follow-up after 2 months, intervention effects were significant for HIV knowledge and to a lesser extent TB knowledge. No significant improvement was found in HIV/STI (sexually transmitted infection) management strategies such as HIV/STI risk behaviour counselling, referral of clients for HIV testing, keeping condoms at stock in church, and church community HIV/AIDS/STI education. It is important to note that faith healers address some of the major known behavioural risk and protective factors such as partner reduction and condom use. Therefore, faith healers could be more widely utilized in HIV prevention programmes as risk reduction counsellors, in particular on matters of community-level education.